REPRESENTATION OF MINANGKABAU CULTURAL VALUES IN THE DESIGN AND MOTIFS OF TAROMPA DATUAK - Irsyad; Bayu Anggara (Universitas Negeri Semarang, 2025)
This study examines how Minangkabau cultural values ​​are represented in the design and motifs of tarompa datuak, which are traditional footwear worn by traditional figures in traditional events. The problem discussed is how the visual symbols of tarompa datuak reflect the traditional wisdom and social values ​​of the Minangkabau people amidst the threat of modernization to their culture. This study uses qualitative methods and an ethnographic approach. This includes interviews with craftsmen and direct observation. The results of the study show that the traditional designs and motifs of tarompa datuak, such as variations of the tarompa datuak design and one of the motifs that is often used, namely the Itiak Pulang Patang motif, which philosophically symbolizes order, togetherness, and local wisdom, illustrate the importance of maintaining harmony and returning to the origin in community life. Not only to beautify, but also to symbolize courage, wisdom, and spirituality that reflect cultural identity. Tarompa datuak is a symbol of culture and a cultural education tool that shows the importance of tradition in the life of the Minangkabau people.